Accomplishment in adversity : a study of practitioner learning in social work - Jones, Martyn (Cranfield University, 1991)
This study is about how people learn to be good social workers. It is based on thirty-seven tape-recorded interviews with practitioners who were selected by -their, peers and each other as doing the job well. The analysis adopts the view that interviews be seen as situated encounters in which interviewees attempt to provide morally adequate accounts of themselves and their actions. This approach is used as a means of making sense of both the 'interview talk' and of the cultural features to which appeal-is made in producing an adequate account. - The analysis is set in a discussion of new theories of adult learning; a crique of professional literature on theory and practice in social work; and, an appraisal of organisational studies of social work. Whilst the professional literature can be criticised for paying scant attention to the organisational settings of social work, the sociological studies can be criticised for failing to comprehend the accomplishments of social workers. This study aims to avoid both of these shortcomings. The literature from new theories of adult learning provides some promising developments in this regard, and the recent trends in the re-organisation of professional training are subjected to scrutiny. On examining the social workers' accounts, it was seen that there were certain central features in common. They were all structured so as to relate the social worker's identity to his or her role, and to relate learning to experience. The differences as well as the similarities in how this is done are clarified by the analysis. In constructing their versions of good social work, the practitioners differed according to their managing of the tension between the formal dimensions of their practice (law, policy, procedure) and their informal, discursive interactions within the everyday worlds of their clients. The accounts of learning given by the social workers refer predominantly to the place of experience, and to membership within collegiate teams. This is viewed as consistent with their ways of constructing good practice, but it is in marked constrast to the versions of learning dominant within the professional literature and educational methods. Ultimately, however, the social workers' own accounts of their learning falter, as they are unable to construct an adequate version for the rigours of formal rationality. The argument is made that this is due to the suppresion of a different reading of social work: social work as 'practice', a practical activity, and a cultural practice. Finally, the implications of this different reading of social work are considered, and reference made to recent major changes in legislation.